The Effectiveness of Science E-Modules for Class VII Junior High Schools Based on Socioscientific Issues to Improve Students' Critical Thinking Skills - Komang Edi Suastrawan; I Nyoman Suardana; A. A. I. Agung Rai Sudiatmika (Universitas Negeri Yogyakarta, 2021)
This study aims to analyze the effectiveness of science e-modules for class VII junior high schools based on socioscientific issues to improve students' critical thinking skills. The type of research used is Pre-Experimental with one group pretest-posttest design. This research was conducted at SMP Negeri 2 Seririt in class VII A with a total of 30 students. Data were collected with 12 items of critical thinking skills test on global warming material through pretest and posttest. Data were analyzed using Paired Sample T-Test and gain score test. The Paired Sample T-Test was used to calculate the significance of increasing students' critical thinking skills, but the gain scores were used to calculate the increase in students' critical thinking skills. The results of this research showed that there was a significant difference in students’ critical thinking skills before and after used science e-module in learning (sig. less than 0.05). The normalized N-gain test also showed an increase in students' critical thinking skills with a value of 0.55 in the medium category. Based on the results of the Paired Sample T-test and the normalized gain score, it can be concluded that the e-module based on socioscientific issues is effectively used to improve students' critical thinking skills.